Neutrophil-to-lymphocyte ratio and chemotherapy response score as prognostic markers in ovarian cancer patients treated with neoadjuvant chemotherapy - M. Liontos (BMC, 2021)
Research highlights Biomarkers that would predict response to neoadjuvant chemotherapy in advanced ovarian cancer patients are eagerly needed: • Neutrophil to Lymphocyte Ratio (NLR) is an indicator of systemic inflammatory response to the malignancy. • NLR was evaluated in 132 patients undergoing Neoadjuvant Chemotherapy for advanced ovarian cancer. • Elevated NLR was associated with worse prognosis. • No association between NLR and response to chemotherapy was noted.